Penerapan Tema Arsitektur Perilaku pada Desain Fasilitas Pendidikan Anak Berkebutuhan Khusus di Surabaya - Ravi Andriyansa; Broto Wahyono Sulistyo; Firdha Ayu Atika (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Education is not only aimed at normal children in general, but children with special needs are also entitled to a proper education. Children with special needs usually go to school in Extraordinary Schools (SLB), but nowadays many regular schools that accept children with special needs to learn with normal children in general so that later can support inclusive educational facilities in their learning, between children with special needs and normal children in general are merged into one. so that children with special needs can adjust to the environment in East Java, especially in the city of Surabaya. But sometimes only one type of child with certain special needs is accepted in the school, thus encouraging researchers to combine all types of children with special needs in one area, while the types of children with special needs are Deaf, Visually Impaired, Visually Impaired. The research method used is qualitative descriptive research and data obtained from field case studies and literature. Design with macro educational concepts so that all designs can be a learning for residents. Micro land order concept is Flexible so that residents can be free to do activities and also easier to move or move around considering this building is a building for children with special needs. Micro concept of shapes is Geometric because geometric shapes are very easy to be known for kindergarten and elementary school children, and also have a variety of shapes such as triangles, circles, squares, etc. So that students can easily recognize the concrete shape of the surrounding buildings. Micro interior concept is Play Based Learning because most students will spend the most time in the room to do their activities. so that with the concept of Play Based Learning Keywords. Children with Special Needs, Education, Inclusive Education Abstrak. Pendidikan yang layak tidak hanya ditujukan kepada anak normal pada umumnya, namun anak berkebutuhan khusus juga berhak memperoleh nya. Sekolah Luar Biasa adalah sekolah khusus untuk anak berkebutuhan khusus. Namun sekarang ini sekolah regular pun juga menerima anak berkebutuhan khusus. Karena itu sekolah regular dituntut untuk menjadi sarana pendidikan inklusif, agar anak berkebutuhan khusus dan anak pada umumnya beraktivitas dalam satu atap. Dalam menerapkan system sekolah inklusif, sekolah regular di Jawa Timur khususnya kota Surabaya kurang memperhatikan kebutuhan anak berkebutuhan khusus. Bahkan hanya salah satu tipe anak berkebutuhan khusus tertentu yang diterima di sekolah tersebut. Hal itu mendorong peneliti untuk memfasilitasi pendidikan dari beberapa tipe anak berkebutuhan khusus dalam satu kawasan, antara lain Tunarungu, Tunanetra, dan Tunagrahita dari jenjang TK dan juga Sekolah Dasar. Metode yang digunakan adalah metode rancangan dengan makro konsep Edukatif agar semua desain bisa menjadi pembelajaran bagi penghuni. Mikro konsep tatanan lahan adalah Fleksibel agar penghuni bisa bebas beraktifitas dan juga lebih mudah bergerak atau berpindah tempat mengingat bangunan ini adalah bangunan untuk anak anak berkebutuhan khusus. Mikro konsep bentuk adalah Geometris karena bentuk geometri sangat mudah dikenal untuk anak TK maupun SD, Mikro konsep interior adalah Play Based Learning.Kata Kunci. Anak Berkebutuhan Khusus, Edukatif, Pendidikan Inklusif